(untitled) (AYUSHDHARA, 2017)
Healing is protective mechanism of our body. In modern science many antibacterial formulations are available with their own limitations. Ayurveda, the Indian traditional system of medicine, is based on empirical knowledge of the observations and the experience over millennia. Ayurveda is a science where there are so many formulations available to treat wound without any complication. Our Acharyas broadly described about treatment principles of wound management and classified the drugs related to Vrana shodhana and Vrana ropana. Classical management of wounds according to Sushruta Samhita follows 60 therapeutic steps, starting with an aseptic dressing of the affected part and ending with the rehabilitation of the normal structure and function. These therapeutic measures were aimed not only to accelerate the healing process but also to maintain the quality and aesthetics of the healing. On comprehensive review of Ayurvedic classics, Durva was found to be one of the drugs having wound healing properties. It is described in Vedas, Charaka Samhita, Sushruta Samhita. In Charaka Samhita, Durva is described in Prajasthapana and Varnya mahakashaya. In Sushruta Samhita, it is described in intrinsic haemorrhage. To rule out its efficacy, a study was carried out in which 30 patients of Sadhyo Vrana were selected for the trail and were subjected to local application of Durvadi Tail. The total effect of the therapy has provided considerably significant relief on the clinical parameters. Durvadi Tail was found to be safe and effective in the management of Sadhyo Vrana by virtue of its antibacterial, analgesic & hemostatic properties.